Erratum to: Measurement of exclusive Υ photoproduction from protons in pPb collisions at s NN = 5.02 TeV (The European Physical Journal C, (2019), 79, 3, (277), 10.1140/epjc/s10052-019-6774-8) - Sirunyan, A. M. (2022)
In this article the author name Luigi Calligaris was incorrectly written as A. Calligaris. The original article has been corrected.